2017
DOI: 10.1101/gr.223313.117
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell gene expression analysis reveals regulators of distinct cell subpopulations among developing human neurons

Abstract: The stochastic dynamics and regulatory mechanisms that govern differentiation of individual human neural precursor cells (NPC) into mature neurons are currently not fully understood. Here, we used single-cell RNA-sequencing (scRNA-seq) of developing neurons to dissect/identify NPC subtypes and critical developmental stages of alternative lineage specifications. This study comprises an unsupervised, high-resolution strategy for identifying cell developmental bifurcations, tracking the stochastic transcript kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 95 publications
7
39
0
Order By: Relevance
“…In our analysis of ~19,000 features across 42 developmental processes and nearly 150,000 single cells, we found that gene counts, or the number of detectably expressed genes per cell, powerfully associates with transcriptional diversity and differentiation status. Although anecdotally observed in specific experimental systems (mouse alveolar epithelial development, zebrafish thrombopoiesis, and neuron differentiation from hESCs [26][27][28] ), we demonstrate for the first time that this association (1) outperforms most stemness inference tools and pre-defined molecular signatures from a compendium of nearly 19,000 RNA-based features, (2) is generally independent of species, platform, and tissue type, and (3) is broadly applicable throughout cellular ontogenesis.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In our analysis of ~19,000 features across 42 developmental processes and nearly 150,000 single cells, we found that gene counts, or the number of detectably expressed genes per cell, powerfully associates with transcriptional diversity and differentiation status. Although anecdotally observed in specific experimental systems (mouse alveolar epithelial development, zebrafish thrombopoiesis, and neuron differentiation from hESCs [26][27][28] ), we demonstrate for the first time that this association (1) outperforms most stemness inference tools and pre-defined molecular signatures from a compendium of nearly 19,000 RNA-based features, (2) is generally independent of species, platform, and tissue type, and (3) is broadly applicable throughout cellular ontogenesis.…”
Section: Discussionmentioning
confidence: 76%
“…To assess these features, we compiled a training cohort consisting of nine gold standard scRNA-seq datasets with experimentally-confirmed differentiation trajectories. These datasets were selected to prioritize commonly used benchmarking datasets from prior studies 12,[18][19][20]26,29 and to ensure a broad sampling of unique developmental states from the mammalian zygote to terminally differentiated cells 26,30 . Overall, the training cohort encompassed 3,174 single cells spanning 49 phenotypes, six tissue types, and three scRNA-seq platforms ( Fig.…”
Section: Rna-based Correlates Of Single-cell Differentiation Statesmentioning
confidence: 99%
“…In this paper, we apply CCSN to Wang dataset [39], which comes from a study of neural progenitor cells (NPCs) that differentiate into mature neurons. The dataset contains six time points over a 30-day period.…”
Section: Resultsmentioning
confidence: 99%
“…Such domains include surveying cell heterogeneity among embryonic stem cells and tumors (Azizi et al 2018;Rosenberg et al 2018), identifying genetic markers of specific cell types (Fan et al 2018), and investigating cell fate commitment and lineage trajectories (Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%